2017
DOI: 10.1136/heartasia-2017-010893
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk in an HIV-infected population in India

Abstract: CVD at younger ages among Asian Indian people living with HIV appear to be an imminent risk for morbidity. Stepping up of preventive services including screening services and prescription of statins are important strategies that must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
(7 reference statements)
3
6
1
1
Order By: Relevance
“…Other authors have reported metabolic alterations, including lower HDL level in HIV-1-infected patients, when compared with healthy donors ( 37 ). Furthermore, the HDL deficiency is a factor that contributes to the high cardiovascular risk observed in patients with HIV-1 ( 38 ) and which is associated with the inflammatory process ( 39 ). Therefore, the aim of this study was to explore the association between HDL levels and the expression of inflammasome components and other inflammatory markers during HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported metabolic alterations, including lower HDL level in HIV-1-infected patients, when compared with healthy donors ( 37 ). Furthermore, the HDL deficiency is a factor that contributes to the high cardiovascular risk observed in patients with HIV-1 ( 38 ) and which is associated with the inflammatory process ( 39 ). Therefore, the aim of this study was to explore the association between HDL levels and the expression of inflammasome components and other inflammatory markers during HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Этот факт объясняется увеличением распространенности традиционных факторов риска, воспалительным и иммунологическим эффектами ВИЧ на эндотелий, а также влиянием АРТ [2,3]. ВИЧ-инфекция является отдельным фактором риска сердечно-сосудистой патологии [4]. У женщин детородного возраста с ВИЧ-инфекцией патология сердечно-сосудистой системы развивается чаще, чем у женщин без ВИЧ-инфекции [5], и интенсивнее, чем у мужчин [6].…”
Section: Hiv-associated Cardiovascular Pathologyunclassified
“…The QRISK score 3 is the latest version and includes both traditional risk factors (age, sex, ethnicity, cholesterol values, systolic blood pressure and antihypertensive treatment, smoking, diabetes, angina in a first-degree relative) and plenty of variables which are not included in other risk scores, such as atrial fibrillation, chronic kidney disease (stage 3, 4, or 5), migraine, corticosteroid therapy, systemic lupus erythematosus (SLE), atypical antipsychotics, severe mental illness, and erectile dysfunction in men [11]. The estimation of CVD risk by QRISK score has been poorly investigated in HIV-infected individuals [12].…”
Section: Introductionmentioning
confidence: 99%